Analisis Metode Make Learning Fun Mahasiswa Kampus Mengajar dalam Pembelajaran di Sekolah Dasar - Muharam, Suhari; Sumarsono, Raden Bambang (Universitas Indraprasta PGRI Jakarta, 2025)
This study aims to analyze the implementation of the Make Learning Fun method applied by students of the Merdeka Mengajar Campus in learning at SDN 4 Bdhan in 2024. This method is designed to create learning that is engaging, interactive, and fun in order to increase students' involvement and enthusiasm for learning. The researchers used a qualitative approach with a descriptive method involving observation, interviews, and documentation as data collection techniques. The results showed three main findings, namely: (1) Ice Breaking is an effective approach to increasing students' readiness and concentration in learning; (2) The focus of learning in this program emphasizes innovation, a learner-characteristic-based approach, and careful planning to create an optimal learning environment; and (3) The optimization of learning media, such as the Math Fun Board and Numeracy Snakes and Ladders, has succeeded in improving students' understanding of the material in a fun and interactive way. In conclusion, the application of the Make Learning Fun method by Teaching Campus students at SDN 4 Bdhan has proven successful in creating learning that attracts attention, is interactive, and fun. Through the use of innovative media, such as the Math Fun Board and Numeracy Snakes and Ladders, as well as an approach tailored to the characteristics of the students, the students succeeded in increasing the motivation and active involvement of the students in the learning process.